Seismic Behavior of Earth Dams With Different Reservoir Water Levels Under Near-Field and Far-Field Earthquakes - Asadi, Masoud; Soltani, Fazlollah; Sinvandi-Pour, Abbas; Noroozinejad Farsangi, Ehsan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The height of reservoir water is one of the important factors affecting the seismic behaviour of earth dams. A large number of earth dams have been constructed in different countries that are sometimes located in a high-risk geographical zone. The studies on the seismic behaviour of earth dams have been conducted for several decades.
Keywords: earthquake; seismic behaviour; earth dam; water levels; finite element modelling; trzęsienie ziemi; badania sejsmiczne; zapora ziemna; poziom wody; modelowanie elementów skończonych